Research progress and challenges of stem cell therapy for Parkinson's disease - Liancheng Zhi (Journal of Clinical Technology and Theory, 2026)
Parkinson's Disease (PD) is a progressive neurodegenerative disorder characterized by the loss of dopaminergic neurons in the substantia nigra, leading to striatal dopamine depletion and resulting motor (e.g., tremor, bradykinesia) and non-motor symptoms (e.g., cognitive decline and sleep abnormalities). Current treatment strategies mainly focus on dopamine replacement therapy and deep brain stimulation. Although these methods can temporarily relieve symptoms, they cannot reverse nerve damage, and long-term use is associated with obvious side effects and potential risks. There is thus an urgent clinical need for new radical treatment methods. Stem cell therapy, leveraging self-renewal, multi-directional differentiation and paracrine regulation, has become a research hotspot in the field of PD treatment, bringing new hope for the radical cure of PD. This review synthesizes the research status and core issues of stem cell therapy for PD, offering practical insights for future research and clinical trials, and promoting the standardization and interdisciplinary development of regenerative neuroscience.